DNA-Polymorphisms and Plasma Levels of Vascular Disease Risk Factors in Greenland Inuit - de Maat, Moniek P. M.; Bladbjerg, Else Marie; Johansen, Lars G.; de Knijff, Peter; Gram, Jørgen; Kluft, Cornelis; Jespersen, Jørgen (Thrombosis and Haemostasis, 1999)
Greenland Inuit are a population with a low risk of cardiovascular disease. Recently, we stated that frequencies of potentially high risk alleles of the apolipoproteins, fibrinogen, factor V, glycoprotein IIIa and factor VII (FVII) genes have different allele frequencies in the Inuit when compared with Caucasian populations. We have extended this study and evaluated whether or not this was also true for the genetic polymorphisms of tissue-type plasminogen activator (t-PA), plasminogen activator inhibitor-1 (PAI-1), angiotensin-converting enzyme (ACE) and angiotensinogen in a group of 133 Greenland Inuit, aged 30-34 y. In addition, we compared the plasma levels of these factors and those of C-reactive protein (CRP) and D-Dimer in Inuit and in Danes, comparable for age and gender. Frequencies (f) were assessed of the alleles that are known as the potential high risk alleles in Caucasians.In the Inuit, the f(insertion allele) of the t-PA intron8ins311 polymorphism was 0.37 (CI 0.32-0.43), the f(4G allele) of the PAI-1 promoter polymorphism was 0.88 (CI 0.83-0.91), the f(deletion allele) of the ACE intron16ins287 polymorphism was 0.40 (CI 0.33-0.47) and the f(M-allele) of the angiotensinogen M/T353 polymorphism was 0.30 (CI 0.25-0.38). As for fibrinogen and FVII polymorphisms, these frequencies are all significantly different from what is reported for Caucasian populations. In the Inuit, plasma levels of fibrinogen and D-Dimer were higher than in the Danes, the PAI-1 levels were lower and FVII, t-PA and CRP levels were comparable. The observed allele frequencies of the polymorphisms of t-PA, fibrinogen, FVII, ACE, angiotensinogen and the plasma levels of PAI-1 and D-Dimer were in accordance with the low CVD risk in the Inuit, considering the observed associations between these measures and CVD risk in Caucasian populations, but for other measures this was not the case (allele frequencies of the PAI-1 polymorphism, and plasma levels of fibrinogen, FVII and t-PA).In conclusion there are clear differences in genetic background and plasma levels of risk factors in Greenland Inuit compared with Caucasian populations, and these differences were sometimes, but not always, in accordance with the observed low cardiovascular disease risk of the Inuit population.